CORPORATE SOCIAL RESPONSIBILITY AND THE SUSTAINABLE DEVELOPMENT- THE PATH AHEAD - Venu, Buddh; S V M, Kama Sai (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate Social Responsibility (CSR) as a concept has transmogrified from a voluntary philanthropic ideal to the holy grail of sustainable development. With the worsening of global environmental and social issues, no businesses can escape from embedding CSR into their approach. The paper establishes the relationship between CSR and sustainable development efforts by highlighting the ways in which corporations can transform environmental sustainability, good governance and economic and social equity. Abstract The paper reviews existing CSR frameworks and analyzing whether they are in tandem with the SDGs and evaluates some of the global best practices. Finally, identifies important omissions in the practice of CSR particularly in developing countries, where governmental systems and stakeholder engagement is inconsistent. It also discusses the influence of government policy, industry standards, and consumer awareness over the future of CSR. Corporate sustainability initiatives should focus on innovation, transparency, and long-term accountability. With the right tools, partnerships, and integrated sustainability in operations, business can be one of the solutions we need to high-potential global development goals. This article concludes by suggesting that a new path forward would see CSR being re-thought as an integrated activity rather than an external one. Citizens, businesses and government need to work together, not only to maximize the power of CSR in promoting sustainable and inclusive growth but also to turn CSR into an integral part of national and local economies.